2021
DOI: 10.1108/jcp-08-2020-0035
|View full text |Cite
|
Sign up to set email alerts
|

Waypoint sequencing: simplifying behaviour sequence analysis for criminal cases

Abstract: Purpose While behaviour sequence analysis (BSA) is popular, it is not without limitations, namely, the level of detail required and time taken to run analyses; therefore, this paper aims to outline a novel method, using 30 serial homicide cases as a worked example. Design/methodology/approach Temporal analysis methods are becoming increasingly popular in applied forensic and criminological research. In recent years, BSA has become a widely used approach. Findings Waypoint sequencing provides a streamlined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…This is where SRs became the analytical score of choice for BSA. An SR provides a measure of whether a transition is occurring more than would be expected by chance and is the most popular form of analytical approach for BSA (Keatley, 2020; Keatley and Clarke, 2020c, 2021; Townsend et al , 2016).…”
Section: Standard Behaviour Sequence Analysis Approachmentioning
confidence: 99%
“…This is where SRs became the analytical score of choice for BSA. An SR provides a measure of whether a transition is occurring more than would be expected by chance and is the most popular form of analytical approach for BSA (Keatley, 2020; Keatley and Clarke, 2020c, 2021; Townsend et al , 2016).…”
Section: Standard Behaviour Sequence Analysis Approachmentioning
confidence: 99%
“…BSA can generate a map showing the progression of behaviors within a particular event or a timespan [41,74]. BSA has been applied in various domains to understand behaviors and social interactions, such as criminal cases [75], nonverbal communication [41], martial interaction [76], and fire evacuation [48]. BSA echoes the concept of Markov models, which focuses on the transitions between behavior pairs [77].…”
Section: Behavioral Sequence Analysismentioning
confidence: 99%
“…For instance, Marono et al [41] produced state transition diagrams of behaviors to exhibit the behavioral sequence of individuals when answering questions. Similarly, Keatley and Clarke [75] proposed a waypoint sequencing diagram to illustrate the key events of criminals in their case histories, providing a simplified sequence of the main behaviors of interest. Also, Nguyen et al [82] demonstrated a visual analytics approach to indicate the behavioral sequence of internet users.…”
Section: Behavioral Sequence Analysismentioning
confidence: 99%